Differences in Biology Students' Perceptions of Self-Efficacy in the Field Entrepreneurship - Yamin, M.; Samsuri, Taufik; Muliadi, Agus (Jurnal Pendidik Indonesia (JPIn), 2023)
This study aims to determine biology students' perceptions of self-efficacy in the field of entrepreneurship. This study is an exploratory research with research subjects of 35 biology education students. The research instrument used was a closed questionnaire with graded answers according to a Likert scale that had been validated by experts and declared valid. The research data analysis used was descriptive statistics and inferential statistics with the Anova test at a significance level of 5%. The results of the study show that (1) students' perceptions of self-efficacy in the field of entrepreneurship have an average student answer score for semester IV of 3,09 in the Good category, semester VI of 3,12 in the Good category, and semester VIII of 3,15 in the Good category. Good category; (2) there is no significant difference in the perception of biology students in semesters IV, VI, VIII regarding self-efficacy in the field of entrepreneurship as evidenced by a significance value of 0,959 which is greater than the alpha test value of 0,05 (0,05).